2010
DOI: 10.1530/rep-09-0187
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ovarian stimulation for IVF on the developing embryo

Abstract: The use of assisted reproductive technologies (ART) has been increasing over the past three decades, and, in developed countries, ART account for 1-3% of annual births. In an attempt to compensate for inefficiencies in IVF procedures, patients undergo ovarian stimulation using high doses of exogenous gonadotrophins to allow retrieval of multiple oocytes in a single cycle. Although ovarian stimulation has an important role in ART, it may also have detrimental effects on oogenesis, embryo quality, endometrial re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
128
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(137 citation statements)
references
References 113 publications
3
128
0
3
Order By: Relevance
“…It has been demonstrated that typically increased LH in PCOS patients suppressed FSH function, promoting premature granulose cells luteinization and follicular atresia in small antral follicles [25][26][27], which all impaired the quality of both oocyte and embryo [28,29]. Indeed, LH levels on day 3 before starting GnRH agonist medication were significantly increased in the high AMH group,and regression analysis indicated LH level was the only independent predictor of IR in our study, so the mostly elevated LH may be contribute to the decreased embryo developmental competence and consequently declined IR in the high AMH group.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that typically increased LH in PCOS patients suppressed FSH function, promoting premature granulose cells luteinization and follicular atresia in small antral follicles [25][26][27], which all impaired the quality of both oocyte and embryo [28,29]. Indeed, LH levels on day 3 before starting GnRH agonist medication were significantly increased in the high AMH group,and regression analysis indicated LH level was the only independent predictor of IR in our study, so the mostly elevated LH may be contribute to the decreased embryo developmental competence and consequently declined IR in the high AMH group.…”
Section: Discussionmentioning
confidence: 99%
“…However, it can affect oocyte maturation and subsequent embryo development. Artificial induction of ovulation with high doses of gonadotrophins has been demonstrated to decrease the viability of embryos and induce oocyte aneuploidy [3,4]. In animal models, COH was shown to induce the incidence of aberrant methylation patterns in mouse two-cell embryos and the placenta [5], and affect sperm methylation patterns in the second generation of offspring [6].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, although pharmacological doses of FSH alone are capable of stimulating ovarian follicular development, LH is strictly necessary to achieve final follicular maturation and oocyte fertilization [4,11]. Standard stimulation regimens typically use exogenous FSH or human menopausal gonadotropin (hMG) in conjunction with gonadotropin-releasing hormone agonists (GnRH-a) to suppress endogenous gonadotropin release [50]. Down-regulation with GnRH-a in some normogonadotrophic women may result in a profound suppression of endogenous LH concentration impairing adequate E 2 synthesis.…”
Section: Introductionmentioning
confidence: 99%